The Herschel* view of the environment of the radio galaxy 4C+41.17 at z = 3.8 - Wylezalek, D.; Vernet, J.; De Breuck, C.; Stern, D.; Galametz, A.; Seymour, Nick; Jarvis, M.; Barthe, P.; Drouart, G.; Greve, T.; Haas, M.; Hatch, N.; et al. (2013)
We present Herschel observations at 70, 160, 250, 350 and 500 μm of the environment of the radio galaxy 4C+41.17 at z = 3.792. About 65 per cent of the extracted sources are securely identified with mid-infrared sources observed with the Spitzer Space Telescope at 3.6, 4.5, 5.8, 8 and 24 μm. We derive simple photometric redshifts, also including existing 850 and 1200 μm data, using templates of active galactic nuclei, starburst-dominated systems and evolved stellar populations. We find that most of the Herschel sources are foreground to the radio galaxy and therefore do not belong to a structure associated with 4C+41.17. We do, however, find that the spectral energy distribution (SED) of the closest (∼25 arcsec offset) source to the radio galaxy is fully consistent with being at the same redshift as 4C+41.17. We show that finding such a bright source that close to the radio galaxy at the same redshift is a very unlikely event, making the environment of 4C+41.17 a special case. We demonstrate that multiwavelength data, in particular on the Rayleigh–Jeans side of the SED, allow us to confirm or rule out the presence of protocluster candidates that were previously selected by single wavelength data sets.